Polishing domestic wastewater on a subsurface flow constructed wetland: organic matter removal and microbial monitoring - Mina, I. Aguiar-Pinto (2012)
Microbial monitoring of constructed wetlands (CWs) treating domestic wastewater is generally scarce, despite the need of more knowledge about its biocenosis. The sanitation quality of a wastewater treated in a CW is a crucial aspect, mainly when the receiving water body is used as a swimming and/or recreation area. The present study was carried out in a horizontal subsurface flow CW planted with Phragmites australis receiving pre-treated domestic wastewater (mean flow 50 m3 day−1), from a population of about 300 inhabitants. The monitoring programme undertaken during the first year operation, revealed removal efficiencies of 61% BOD5, 44% COD, and 65% TSS for inlet water with ca. 90 mg L−1 BOD5, 157 mg L−1 COD, and 17 mg L−1 TSS. Total Coliform (TC) and Faecal Coliform (FC) bacteria were removed from wastewater (mean inlet values of 5 × 106 CFU 100 mL−1 TC and of 9 × 105CFU 100 mL−1 FC), with efficiencies of 92 and 97%, respectively. The dynamics of microbial communities established in the system assessed by polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE), had revealed a high bacterial diversity within the system, with no relevant differences in composition at the CW inlet and outlet but exhibiting temporal differences in bacterial communities.